PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MIT APP INVENTOR UNTUK KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA DI SMK NEGERI 3 SURABAYA - Krisdianto, Muhammad; Sumbawati, Meini Sondang; Harimurti, Rina; Zuhrie , Muhammad Syariffuddien (Jurnal Pendidikan Teknik Elektro, 2027)
This study was motivated by the low interest in learning and difficulties experienced by students in understanding logic gates and Boolean algebra in conventional learning at SMK Negeri 3 Surabaya. This condition has an impact on the suboptimal critical thinking skills that should be the main focus of the Merdeka Curriculum in accordance with the Pancasila Student Profile dimension. To overcome this problem, interactive learning media based on MIT App Inventor was developed, which can be accessed via smartphones and contains materials, videos, practical simulations, and evaluations based on Higher Order Thinking Skills (HOTS). The study aimed to analyze four aspects, namely the level of media validity, student responses, the effectiveness of the media for critical thinking skills, and the relationship between student responses and critical thinking skills. The development used the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model with 34 students from class X TAV 3 as subjects. The research design used a One-Shot Case Study with data collection techniques through expert validation questionnaires, student response questionnaires, and HOTS-based multiple-choice tests. The results showed that the media validity level was 96.35% (highly valid), student response was 83.61% (strongly agree), and the average post-test score was 86.79 (very high). The Product Moment correlation test produced a coefficient of 0.626 with a significance of < 0.05, indicating a significant relationship between student responses and critical thinking skills. Thus, MIT App Inventor-based interactive learning media proved to be valid, responsive, and effective when applied in Basic Electricity and Electronics learning.